DEVELOPMENT OF LANGUAGE COMPETENCE BY TEACHING FOREIGN LANGUAGE FOLKLORE GENRES IN STUDENTS - Yunusova Sojida Mamadaliyevna (Лучшие интеллектуальные исследования, 2023)
Annotation: This article explores the impact of incorporating foreign language folklore genres into the curriculum as a method to enhance language competence among students. Through a comprehensive literature analysis, we delve into the theoretical foundations, followed by a detailed examination of the methods employed and the subsequent results obtained. The discussion section critically evaluates the findings, offering insights into the effectiveness of this pedagogical approach. The article concludes with implications for future language teaching practices and suggestions for further research.